2010
DOI: 10.1159/000276982
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Gap Junction Channels Are Upregulated by Metoprolol: An Unexpected Effect of Beta-Blockers

Abstract: Background/Aims: Since β-adrenoceptors have been shown to affect cardiac gap junction channels, we wanted to elucidate the possible effect of metoprolol on the gap junction protein connexin-43, using racemic RS-metoprolol or the isomer R-metoprolol (no β-adrenoceptor blockade) or S-metoprolol (β1-adrenoceptor blocker). Methods: Cultured neonatal rat cardiomyocytes were exposed to either RS-metoprolol or R-metoprolol or S-metoprolol (0.1 µmol/l each) without or with additional isoprenaline (0.1 µmol/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…The antifibrillatory effect of melatonin may be mainly attributed to its ability to prevent connexin‐43 lateralization. Moreover, other antiarrhythmic agents, such as metoprolol, lead to a lower degree of lateralization and lower transverse conduction velocity . Furthermore, our results indicated that melatonin receptor activation is necessary to prevent connexin‐43 lateralization and arrhythmias that require reentry to persist.…”
Section: Discussionmentioning
confidence: 70%
“…The antifibrillatory effect of melatonin may be mainly attributed to its ability to prevent connexin‐43 lateralization. Moreover, other antiarrhythmic agents, such as metoprolol, lead to a lower degree of lateralization and lower transverse conduction velocity . Furthermore, our results indicated that melatonin receptor activation is necessary to prevent connexin‐43 lateralization and arrhythmias that require reentry to persist.…”
Section: Discussionmentioning
confidence: 70%
“…These results also indicate that metoprolol can reduce the number of contraction in a given time, possibly reflecting an improved contraction force; they may represent some of the beneficial factors contributing to the protective effects on DCM iPSC-CMs. In addition, metoprolol treatment on cultured neonatal rat CMs have been shown to upregulate protein levels of cardiac gap junction channels (47), allowing a better connection and communication between cells. Altogether, these may exert beneficial effects on the DCM iPSC-CMs observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that α‐ and β‐adrenoceptor stimulation up‐regulated the expression of Cx43 (Salameh et al ., 2006, 2008; Rojas Gomez et al ., 2008) and mechanical stretch enhanced the expression of Cx43 and altered Cx43 localization (Salameh et al ., 2010a). Moreover, in a cell culture study, we have found enhanced Cx43 expression in cells treated with metoprolol (Salameh et al ., 2010b). Thus, we proposed the hypothesis that β‐adrenoceptor antagonists may have an effect on connexin expression and/or on connexin localization.…”
Section: Introductionmentioning
confidence: 90%